2017
DOI: 10.1108/ci-07-2016-0040
|View full text |Cite
|
Sign up to set email alerts
|

Innovation development and adoption in small construction firms in Ghana

Abstract: Purpose The purpose of this research is to identify the conditions under which the internal environment of small construction firms makes them either develop or adopt an innovation. Design/methodology/approach The research described in this paper adopted a qualitative case study approach. The data were obtained from multiple sources such as face-to-face semi-structured interviews with company representatives and from project reports. Findings The study identified that firms’ decision to either adopt or dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
(124 reference statements)
1
12
0
Order By: Relevance
“…Subsequently, lower levels of barriers contribute positively to the innovation process. This relation is consistent with literature [2,3]. The graph represents an exponential decay behaviour created by a reinforcing loop.…”
Section: Stage 3: Dynamic Model Formulationsupporting
confidence: 80%
See 1 more Smart Citation
“…Subsequently, lower levels of barriers contribute positively to the innovation process. This relation is consistent with literature [2,3]. The graph represents an exponential decay behaviour created by a reinforcing loop.…”
Section: Stage 3: Dynamic Model Formulationsupporting
confidence: 80%
“…The construction sector plays a key role in any country's economy. However, the innovation implementation process in the construction industry has been extremely slow [2][3][4][5]. One of the reasons is a significant gap between the creation of theoretical foundations for technology within R&D and their absorption and application in mass production.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, it was observed that small and medium companies pay less attention to KM and innovation compared to large companies (Park et al , 2013; Dansoh et al , 2017). It is observable that small companies are at a disadvantage on the technology and technical expertise front (Jeffcoate et al , 2000), but a broad range of knowledge, skills and technology are crucial for the company to perform multiple tasks and remain healthy (Sexton and Barret, 2003; Boyd et al , 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, a high level of innovation performance is extremely important for the industry's growth and the development a country economy. Many studies have been undertaken to examine innovationrelated topics in the field of construction management (Egbu 2004;Stewart 2007;Panuwatwanich et al 2008Panuwatwanich et al , 2009aPanuwatwanich et al , 2009bDavidson 2013;Ozorhon 2013;Davis et al 2016;Dansoh et al 2017;Yusof et al 2017). It is worth noting, that most of the aforementioned studies have addressed innovation processes in the industry by mainly focusing at the project and firm level.…”
Section: Construction Innovation Processesmentioning
confidence: 99%